Relationship Between Organizational Resources, Capabilities and Systems on Competitive Advantage and Performance of Malaysian Manufacturers - Ismail, 'Alimin Ismadi (2010)
In spite of the importance of attaining competitive advantage in organizations, there has been limited study on the relationship between organizational resources and the way firms are organized to achieve competitive advantage. As such, critics argue that more empirical research is needed in the area of competitive advantage as past studies have concentrated mainly on the attributes of resources and capabilities leading to competitive advantage. They have neglected the important, if not arguably more essential, issue of the relative strength or magnitude of relationship between these variables. As far as competitive advantage from the resource-based view RBV) of the firm isconcerned, this has created a gap in the body of knowledge and also between the theoretical and practical aspect of managing organizations. The objective of this research is to examine the relationship between organizational resources, capabilities and systems, and their effects on competitive advantage and performance ofMalaysian manufacturers. This research was conducted among manufacturers listed in the Federation of Malaysian Manufacturers Directory 2008. A cross-sectional study using structured questionnaire was used to obtain responses from the manufacturers. A pilot study was initially conducted to establish the reliability of the questionnaire scales and measurements. From the subsequent actual survey, 127 respondents replied and completed the questionnaire (12.7% response rate). Exploratory data analysis was initially conducted to ensure there is no violation of the assumptions of normality, linearity, homogeneity of variance, multicollinearity and homoscedasticity which are amongst the conditions needed in the multivariate data analysis. The confirmatory factor analysis conducted via the structural equation modeling (SEM) technique indicated that the model of relationship between the research variables fits the data well. Apart from the SEM approach, this study also utilized bivariate correlation, simple linear regression and multiple linear regression to examine the relationship between the research variables. In addition, hierarchical multiple regression and twoway ANOVA and/or moderated multiple regression were also employed to test the mediating and moderating effects respectively. Based on the bivariate correlations, this research has verified that there is a significant positive and linear relationship between organizational resources, capabilities and systems. In addition, the SEM approach and/or multiple linear regression showed that there is a significant positive relationship between organizational capabilities, systems and competitive advantage, and also between organizational resources, systems and performance. The simple linear regression revealed that there is a significant positive relationship between organizational competitive advantage and performance. However, by applying the SEM technique and hierarchical multiple regression, competitive advantage is identified as a non-significant mediator in the relationship between organizational resources, capabilities, systems and performance. Only firms’ age is identified as a significant moderator in the relationship between competitive advantage and performance, and such a relationship is stronger for the old firms compared to the new firms. Despite the non-significant moderating effects of firms’country of origin, size and product destination in the relationship between competitive advantage and performance, overall this study has managed to provide empirical evidence, support and insight of the perception of Malaysian manufacturers on the issue of competitive advantage from the RBV. In short, this study has contributed to the literature, practice and policy of strategically managing organizational resources, capabilities and systems towards the attainment of competitive advantage and performance level.